Method for improving semiconductor photoelectrochemical cathodic protection of metal with poor corrosion resistance

By covering the organic coating on the surface of the metal with poor corrosion resistance, the self-corrosion potential of the metal is regulated, and the problem of low protection efficiency of the metal with poor corrosion resistance in photoelectrochemical cathode protection is solved, thereby achieving efficient protection of the metal with poor corrosion resistance.

CN119571333AActive Publication Date: 2025-03-07UNIV OF SCI & TECH BEIJING +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411537723.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-07
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Metals with poor corrosion resistance have low protection efficiency in photoelectrochemical cathode protection, which restricts their application in anti-corrosion engineering.

Method used

The surface of the metal with poor corrosion resistance is completely covered with organic coating, and its physical shielding effect is used to regulate the self-corrosion potential of the metal, and promote the transfer of electrons generated by semiconductor photoanode photo to the metal.

Benefits of technology

The photoelectrochemical cathode protection efficiency of semiconductor photoanode on metals with poor corrosion resistance is improved, and efficient protection of metals with poor corrosion resistance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571333A_ABST
    Figure CN119571333A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving semiconductor photoelectrochemical cathode protection poor-corrosion-resistance metal, and relates to the field of metal material corrosion and protection. Aiming at the problem that semiconductor photo-induced electrons are difficult to transmit to a metal surface with poor corrosion resistance in a photoelectrochemical cathodic protection technology, the method comprises the following steps: preparing an organic coating, preparing a semiconductor photo-anode and realizing the photoelectrochemical cathodic protection technology. According to the method, the self-corrosion potential of the metal with the poor corrosion resistance can be regulated and controlled, semiconductor photo-induced electrons are promoted to be transmitted to the metal, and the photoelectrochemical cathode protection technology is applied to the metal with the poor corrosion resistance. The method is simple, effective and easy to operate, the application range of the photoelectrochemical cathode protection technology is expected to be expanded, the protection efficiency of the technology on metal is improved, and the protection time of the technology on metal is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal corrosion and protection, and in particular relates to a method for improving the metal with poor corrosion resistance of semiconductor photoanode photoelectrochemical cathode protection. Background Art

[0002] Photoelectrochemical cathodic protection technology is a green, low-carbon, and sustainable anti-corrosion strategy. However, the photocathodic protection efficiency of metals or alloys with poor corrosion resistance, such as carbon steel, is low, which restricts its application in anti-corrosion engineering. Improving the photocathodic protection efficiency of metals with poor corrosion resistance has become a research hotspot and difficulty in this field, which is of great significance to metal corrosion engineering.

[0003] Photoelectrochemical cathodic protection technology uses sunlight as energy to stimulate the transfer of photogenerated electrons from semiconductors to the metal surface, causing the metal to undergo cathodic polarization and thus slowing down or inhibiting its corrosion. Based on semiconductors, the photoelectrochemical protection process of solar energy conversion mainly includes three key steps: light absorption by semiconductors, carrier separation and migration by semiconductors, and transmission of photogenerated electrons from the semiconductor surface to the protected metal. Its efficiency is determined by the synergistic effect of the three steps. Therefore, the direction and efficiency of photoelectron transmission between semiconductors and metals have an important influence on the mechanism of action of semiconductors in the corrosion of metals with poor corrosion resistance.

[0004] The prerequisite for photoelectron transmission to metal is that the semiconductor quasi-Fermi level is negative to the self-corrosion potential of the metal. The matching degree between the semiconductor quasi-Fermi level and the self-corrosion potential of the metal is the key to photoelectron transmission. Existing research is mostly based on the optimization design of the composition and structure of semiconductor photoanode materials, and the photocurrent between the semiconductor and the metal is improved by regulating the semiconductor band structure. At present, it is difficult to meet the demand for protection efficiency by regulating the semiconductor band structure alone. However, there are few reports on the construction of a coupled system of semiconductor photoanode-physical protection metal from the perspective of the protected metal, and such technology is still lacking. It is well known that the more positive the self-corrosion potential of the metal, the easier it is for the semiconductor photoelectron to be transmitted to the metal, and the easier it is to achieve photoelectrochemical protection. Therefore, on the basis of regulating the semiconductor band structure, improving the self-corrosion potential of the metal will hopefully promote the solution of key issues in photoelectrochemical cathodic protection technology, and realize the advantages of semiconductors in metal corrosion protection to meet practical application needs. Summary of the invention

[0005] The present invention aims to provide a method for improving the semiconductor photoanode photoelectrochemical cathode protection of metals with poor corrosion resistance. The method is to completely cover the surface of the metal with poor corrosion resistance with an organic coating. The wrapping effect of the organic coating is used to shift the self-corrosion potential of the metal positively. Under the regulation of the organic coating, semiconductor photoelectrons are more easily transferred to the metal, thereby improving the semiconductor photoelectrochemical cathode protection efficiency and achieving efficient protection of metals with poor corrosion resistance.

[0006] The above object of the present invention is achieved through the following technical solutions:

[0007] A method for improving the semiconductor photoanode photoelectrochemical cathode protection of metals with poor corrosion resistance, including the preparation of an organic coating, the preparation of a semiconductor photoanode, and the realization of a photoelectrochemical cathode protection technology. Under the physical shielding effect of the organic coating, the self-corrosion potential of the metal with poor corrosion resistance is effectively regulated, which promotes the transfer of photogenerated electrons from the semiconductor photoanode to the metal. This method significantly improves the overall performance of the semiconductor photoelectrochemical cathode protection of metals with poor corrosion resistance.

[0008] The technical solution adopted by the present invention is: a method for improving the corrosion resistance of metals with poor photoelectrochemical cathode protection by semiconductor photoanode, comprising the following steps:

[0009] (1) Preparation of organic resin:

[0010] The organic coating is prepared on the surface of metal with poor corrosion resistance by using preparation processes such as brushing, spraying, dipping, electrophoretic coating, and electrostatic spraying. The organic coating is cured at room temperature. The purpose is to form an organic coating protective film with physical shielding effect on the surface of metal with poor corrosion resistance.

[0011] Metals with poor corrosion resistance should be mechanically polished and cleaned with organic solvents before use. Use sandpaper to polish the metal surface until there are no obvious scratches on the surface; use organic solvents to ultrasonically clean the sample. The purpose is to remove impurities such as dust and oxide film attached to the metal surface.

[0012] A position not covered by the organic coating is reserved on the top of the corrosion-resistant metal surface for copper wire connection;

[0013] The organic coating comprises acrylic resin, epoxy resin and silane coupling agent;

[0014] The metals with poor corrosion resistance include iron and its alloy materials.

[0015] (2) Preparation of semiconductor photoanode:

[0016] Using conductive material as substrate and sealing the top with polytetrafluoroethylene tape, a high-efficiency semiconductor photoanode is prepared on the conductive substrate by using semiconductor thin film preparation methods such as hydrothermal method, solvent thermal method, oxidation method, sol-gel method, chemical vapor deposition, physical vapor deposition, or a combination of the above methods.

[0017] The conductive material includes FTO (fluorine-doped tin oxide) conductive glass, ITO (indium tin oxide) conductive glass, and titanium plate;

[0018] The top of the conductive material is packaged with polytetrafluoroethylene tape, the purpose of which is to prevent the semiconductor film from covering the conductive substrate.

[0019] The semiconductor photoanode includes a single-element semiconductor, an oxide semiconductor, a sulfide semiconductor, a nitride semiconductor, a phosphide semiconductor and a composite thereof.

[0020] (3) Implementation of photoelectrochemical cathodic protection technology

[0021] The semiconductor is directly irradiated with sunlight or simulated sunlight to induce the semiconductor to generate photogenerated electrons. The photoanode and the metal with poor corrosion resistance are connected by copper wire to establish an electron transmission channel between the semiconductor and the metal with poor corrosion resistance, thereby realizing the photoelectrochemical cathodic protection of the metal with poor corrosion resistance by the semiconductor photoanode.

[0022] The copper wire connection method is that iron alligator clips are welded at both ends of the copper wire, one alligator clip is clamped to the substrate conductive surface of the photoanode not covered with the semiconductor film, and the other alligator clip is clamped to the metal surface not covered with the organic coating.

[0023] Furthermore, the preparation of the semiconductor photoanode comprises the following steps:

[0024] 1) The FTO conductive glass is immersed in a mixture containing titanium dioxide and dopamine and heated. After drying, a TiO2@PDA film is obtained on the surface of the FTO conductive glass;

[0025] The mass ratio of dopamine hydrochloride, titanium dioxide and hexamethylenetetramine in the titanium dioxide and dopamine mixed solution is (0.1-0.2): (2-4): 1;

[0026] The FTO conductive glass is inserted into the mixture of titanium dioxide and dopamine, and an area is reserved on the liquid surface and is not inserted into the mixture;

[0027] 2) pouring the indium sulfide precursor solution into a high-pressure reactor, heating for reaction, cooling, washing with deionized water, and drying to obtain indium sulfide nanoparticles;

[0028] The indium sulfide precursor solution is an aqueous solution of indium nitrate and thioacetamide, wherein the mass ratio of indium nitrate to thiourea is (2-3):1;

[0029] 3) Ultrasonically uniformly dispersing indium sulfide nanoparticles in an ethanol solution to obtain an indium sulfide ethanol solution, wherein the concentration of the indium sulfide ethanol solution is (1-2) g / L; drop-coating the indium sulfide ethanol solution on the TiO2@PDA film on the conductive surface of the FTO glass and drying it; then placing the sample with the conductive surface facing upward in a muffle furnace and maintaining it at 300-400°C for 20-40 minutes to obtain an In2S3 / TiO2@PDA semiconductor photoanode.

[0030] Furthermore, a method for improving the corrosion resistance of metals with poor corrosion resistance by semiconductor photoanode photoelectrochemical cathode protection comprises the following steps:

[0031] (1) Preparation of silane coupling agent coating

[0032] The poorly corrosion-resistant metal Q235 carbon steel is mechanically polished and cleaned with an organic solvent before use. The poorly corrosion-resistant metal is immersed in a mixed liquid containing a silane coupling agent and heated in a water bath. The poorly corrosion-resistant metal sheet is suspended in the mixed liquid of the silane coupling agent, a certain area is reserved on the liquid surface, and the rest of the metal is vertically inserted into the mixed liquid.

[0033] Then place it in a vacuum drying oven and dry it under vacuum.

[0034] The silane coupling agent mixture was prepared by adding 0.30 mL of silane coupling agent (KH550) to 50 mL of ethanol and water mixture (volume ratio 1:10), followed by ultrasonic treatment.

[0035] (2) Preparation of indium sulfide semiconductor photoanode:

[0036] The indium sulfide semiconductor photoanode was prepared by a hydrothermal method. The indium sulfide precursor solution and FTO conductive glass were placed in a high-pressure reactor with a polytetrafluoroethylene substrate, heated for reaction, cooled, and rinsed with deionized water to obtain an indium sulfide semiconductor film on the surface of the FTO conductive glass.

[0037] The indium sulfide precursor solution is prepared by completely dissolving indium nitrate powder and thiourea powder in deionized water, wherein the mass ratio of the indium nitrate powder to the thiourea powder is 2:1.

[0038] Before placing the FTO conductive glass in the reactor lining, the top needs to be wrapped with raw tape; the purpose is to reserve the conductive surface on the top that is not covered by the sample to facilitate the subsequent connection of the copper wire.

[0039] (3) Photoelectrochemical cathodic protection

[0040] The indium sulfide semiconductor photoanode is directly irradiated with sunlight or simulated sunlight to induce indium sulfide to generate photogenerated electrons. The conductive surface of FTO conductive glass and the surface of Q235 carbon steel are connected by copper wire to establish an electron transmission channel between the semiconductor and carbon steel, thereby realizing the photoelectrochemical cathodic protection of Q235 carbon steel by the indium sulfide semiconductor photoanode.

[0041] The copper wire connection method is to use a copper wire with iron alligator clips at both ends, one alligator clip is clamped to the part of the FTO conductive glass not covered with indium sulfide, and the other alligator clip is clamped to the part of the Q235 carbon steel not covered with the silane coupling agent.

[0042] Furthermore, a method for improving the corrosion resistance of metals with poor corrosion resistance by semiconductor photoanode photoelectrochemical cathode protection comprises the following steps:

[0043] (1) Preparation of water-based acrylic coating

[0044] Metals with poor corrosion resistance (Q345 carbon steel) are mechanically polished and cleaned with organic solvents before use; a water-based acrylic resin coating is prepared on the surface of the metal with poor corrosion resistance using a brushing process, and the water-based acrylic resin is applied to the front, side and bottom of the metal with poor corrosion resistance. The water-based acrylic resin is not applied to the top of the metal, and an area is reserved.

[0045] (2) Preparation of indium sulfide / polydopamine / titanium dioxide composite photoanode:

[0046] The FTO conductive glass is immersed in a mixture containing titanium dioxide and dopamine, heated for reaction, cooled and dried, and a TiO2@PDA film is obtained on the surface of the FTO conductive glass.

[0047] The titanium dioxide and dopamine mixed solution was prepared by adding 5 mL of deionized water, 0.015 g of dopamine hydrochloride and 0.20 g of titanium dioxide into a round-bottom flask, and ultrasonically treating for 30 min. Then, 0.1 g of hexamethylenetetramine powder was added and dissolved in the solution and mixed evenly to obtain a titanium dioxide and dopamine mixed solution.

[0048] The indium sulfide precursor solution is poured into a high-pressure reactor with a polytetrafluoroethylene substrate, heated for reaction, cooled, washed with deionized water, and freeze-dried to obtain indium sulfide nanoparticles.

[0049] The indium sulfide precursor solution was prepared by completely dissolving indium nitrate and thioacetamide in 25 mL of deionized water, wherein the masses of indium nitrate powder and thiourea powder were 0.027 g and 0.01 g, respectively.

[0050] The prepared indium sulfide nanoparticles were evenly dispersed in an ethanol solution and drop-coated on the TiO2@PDA film on the conductive surface of the FTO glass. The sample was placed in a muffle furnace and heated for a certain period of time.

[0051] The FTO conductive glass is suspended above the mixture of titanium dioxide and dopamine, a certain area is reserved on the liquid surface, and the rest of the FTO conductive glass is vertically inserted into the mixture.

[0052] Before use, FTO conductive glass needs to be ultrasonically cleaned with acetone and ethanol for 3 times each. The surface is clean and free of impurities, and then blown dry with nitrogen for later use.

[0053] (3) Photoelectrochemical cathodic protection:

[0054] The indium sulfide / polydopamine / titanium dioxide composite photoanode semiconductor photoanode is directly irradiated with sunlight or simulated sunlight to induce indium sulfide to generate photogenerated electrons. The conductive surface of FTO conductive glass and the surface of Q345 carbon steel are connected by copper wire to establish an electron transmission channel between the semiconductor and carbon steel, thereby realizing the photoelectrochemical cathodic protection of Q345 carbon steel by the indium sulfide semiconductor photoanode.

[0055] The FTO conductive glass and Q345 carbon steel are connected by copper wires and are considered as a conductive whole. The copper wire connection method is to use a copper wire with iron alligator clips at both ends, one alligator clip is clamped to the part not covered by the FTO conductive glass, and the other alligator clip is clamped to the part of the Q345 carbon steel not covered by the water-based acrylic resin.

[0056] Beneficial effects of the present invention:

[0057] Without destroying the metal structure and surface composition, the organic coating can be directly prepared on the metal surface. Under light excitation, the semiconductor valence band electrons in the photoanode will jump to the conduction band. Through the conductive connection, the electrons on the semiconductor photoanode migrate to the metal surface, causing the metal to undergo cathodic polarization and inhibiting its electrochemical dissolution. Due to the introduction of the organic coating on the metal surface, the self-corrosion potential of metals with poor corrosion resistance is increased, and the electrons in the photoanode are easily migrated to the metal surface under the action of the potential difference. Therefore, the physical shielding effect of the organic coating has a significant promoting effect on the photoelectrochemical cathodic protection performance of the semiconductor photoanode for metals with poor corrosion resistance. In addition, in the absence of light, the organic coating is densely and firmly attached to the metal surface, which can also prevent the corrosive medium from penetrating into the metal, providing physical protection for the metal.

[0058] 1. The organic coating in the present invention forms a physical barrier on the surface of the metal with poor corrosion resistance to prevent the dissolution of the metal. The addition of the organic coating in the photoelectrochemical cathodic protection enables the semiconductor photoanode to exhibit excellent performance. With the help of the organic coating, the self-corrosion potential of the metal with poor corrosion resistance is effectively regulated, the electron transmission channel between the semiconductor and the metal with poor corrosion resistance is opened, the transfer of semiconductor photogenerated electrons to the metal is promoted, and the photoelectrochemical cathodic protection ability of the semiconductor photoanode to the metal with poor corrosion resistance is improved.

[0059] 2. The preparation method involved in the present invention is simple and mild, does not affect the metal surface structure, and the organic composite coating is dense and firmly attached to the metal surface. In addition to being conducive to the implementation of photoelectrochemical cathodic protection technology in metals with poor corrosion resistance, the physical shielding effect of the coating on the corrosive medium can also inhibit the corrosion of the metal in the absence of light, further improving the protective effect of the technology on the metal.

[0060] 3. The present invention is used to improve the photoelectrochemical cathodic protection corrosion resistance of metals with poor corrosion resistance. This technology shows excellent performance in metals with poor corrosion resistance of photoelectrochemical cathodic protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 The photocurrent-time curve and the photovoltage-time curve of the indium sulfide photoelectrochemical cathodic protection Q235 carbon steel system prepared in Example 1 of the present invention and Comparative Example 1 are shown.

[0062] Figure 2The photocurrent-time curve and photovoltage-time curve of the indium sulfide / polydopamine / titanium dioxide composite layer photoelectrochemical cathodic protection Q345 carbon steel system prepared in Example 2 of the present invention and Comparative Example 2 are shown. DETAILED DESCRIPTION

[0063] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described herein are only for illustrating and explaining the present invention and are not limited to the present invention.

[0064] Example 1

[0065] (1) Preparation of silane coupling agent coating

[0066] The metal with poor corrosion resistance was immersed in a mixture containing a silane coupling agent and heated in a 60°C water bath for 2 h, and then placed in a vacuum drying oven at 80°C for 12 h.

[0067] The silane coupling agent mixture was prepared by adding 50 mL of ethanol and water mixture (volume ratio 1:10) into a 100 mL round-bottom flask, stirring and mixing, adding 0.30 mL of silane coupling agent (KH550), and ultrasonically treating for 30 min.

[0068] The metal sheet is suspended above the silane coupling agent mixture, with a reserved area of ​​10 mm*8 mm on the liquid surface, and the rest of the metal is vertically inserted into the KH550 mixture.

[0069] The metal with poor corrosion resistance is Q235 carbon steel with a size of 10 mm*25 mm*1.5 mm.

[0070] Q235 carbon steel was mechanically polished and cleaned with organic solvents before use. The metal surface was polished with 200 mesh, 400 mesh, and 800 mesh sandpaper in turn until there were no obvious scratches on the surface; the sample was ultrasonically cleaned with anhydrous ethanol and acetone organic solvents in turn for 15 minutes. After cleaning, the sample surface was blown dry with nitrogen and placed in a vacuum drying oven at 50°C for 6 hours. The purpose is to remove impurities such as dust and oxide film attached to the metal surface.

[0071] (2) Preparation of indium sulfide semiconductor photoanode:

[0072] Indium sulfide semiconductor photoanode was prepared by hydrothermal method.

[0073] The indium sulfide precursor solution and FTO conductive glass were placed in a high-pressure reactor with a capacity of 50 mL of polytetrafluoroethylene substrate, heated at 180°C for 8 h, cooled, and rinsed with deionized water to obtain an indium sulfide semiconductor film on the surface of the FTO conductive glass.

[0074] The indium sulfide precursor solution is prepared by completely dissolving indium nitrate powder and thiourea powder in 25 mL of deionized water, wherein the masses of indium nitrate powder and thiourea powder are 0.045 g and 0.023 g, respectively.

[0075] The size of FTO conductive glass is 10 mm*25 mm*2 mm.

[0076] Before use, FTO conductive glass needs to be ultrasonically cleaned with acetone and ethanol for 3 times each. The surface is clean and free of impurities, and then blown dry with nitrogen for later use.

[0077] Before placing the FTO conductive glass in the reactor lining, the top needs to be wrapped with raw tape; the purpose is to reserve the conductive surface on the top that is not covered by the sample to facilitate the subsequent connection of the copper wire.

[0078] The FTO conductive glass is placed in the reactor lining with the conductive surface facing downward against the inner wall of the reactor and immersed in the mixed precursor solution.

[0079] The indium sulfide semiconductor film was rinsed with deionized water and then dried at 50 °C under vacuum for 6 h.

[0080] (3) Implementation of photoelectrochemical cathodic protection technology

[0081] The indium sulfide semiconductor photoanode is directly irradiated with sunlight or simulated sunlight to induce indium sulfide to generate photogenerated electrons. The conductive surface of FTO conductive glass and the surface of Q235 carbon steel are connected by copper wire to establish an electron transmission channel between the semiconductor and carbon steel, thereby realizing the photoelectrochemical cathodic protection of Q235 carbon steel by the indium sulfide semiconductor photoanode.

[0082] The FTO conductive glass and Q235 carbon steel are connected with copper wire and regarded as a conductive whole.

[0083] The copper wire connection method is to use a copper wire with iron alligator clips at both ends, one alligator clip is clamped to the part of the FTO conductive glass not covered with indium sulfide, and the other alligator clip is clamped to the part of the Q235 carbon steel not covered with the silane coupling agent.

[0084] Example 2

[0085] (1) Preparation of water-based acrylic coating

[0086] The water-based acrylic resin coating was prepared on the carbon steel surface by brushing process.

[0087] The front, side and bottom surfaces of the metal with poor corrosion resistance are coated with water-based acrylic resin, and the top of the metal front surface is not coated with water-based acrylic resin, and the reserved area is 10 mm*8 mm.

[0088] The thickness of the water-based acrylic resin coating on the front of the metal is about 40 μm. The four corners and bottom of the metal are completely covered, and the resin coating is ensured to be uniform. It is cured at room temperature for 7 days.

[0089] The back of the metal is coated with water-based acrylic resin, and the top of the back of the metal where the water-based acrylic resin is not coated corresponds to the front and has the same area as the front.

[0090] Control the thickness of the water-based acrylic resin coating on the back of the metal to be consistent with that on the front, and ensure that the resin is evenly coated and cured at room temperature for 14 days.

[0091] The water-based acrylic resin is a common type of acrylic resin (styrene acrylic), and the manufacturer and model purchased is Donglian Chemical 1065.

[0092] The metal with poor corrosion resistance is Q345 carbon steel with a size of 10 mm*25 mm*1.5 mm.

[0093] Q345 carbon steel was mechanically polished and cleaned with organic solvents before use. The metal surface was polished with 200 mesh, 400 mesh, and 800 mesh sandpaper in turn until there were no obvious scratches on the surface; the sample was ultrasonically cleaned with anhydrous ethanol and acetone organic solvents in turn for 15 minutes. After cleaning, the sample surface was blown dry with nitrogen and placed in a vacuum drying oven at 50°C for 6 hours. The purpose is to remove impurities such as dust and oxide film attached to the metal surface.

[0094] (2) Preparation of In2S3 / TiO2@PDA semiconductor photoanode:

[0095] The FTO conductive glass was immersed in a mixture of titanium dioxide and dopamine and heated at 90°C for 3 h, and then placed in a vacuum drying oven at 60°C for 6 h to obtain a TiO2@PDA film on the surface of the FTO conductive glass.

[0096] The titanium dioxide and dopamine mixed solution was prepared by adding 5 mL of deionized water, 0.015 g of dopamine hydrochloride and 0.20 g of titanium dioxide into a 25 mL round-bottom flask, and ultrasonically treating for 30 min. Then, 0.1 g of hexamethylenetetramine powder was added and dissolved in the solution and mixed evenly to obtain a titanium dioxide and dopamine mixed solution.

[0097] The indium sulfide precursor solution was poured into a 50 mL polytetrafluoroethylene-lined autoclave, heated at 150°C for 1 h, cooled, washed with deionized water, and freeze-dried.

[0098] The indium sulfide precursor solution was prepared by completely dissolving indium nitrate and thioacetamide in 25 mL of deionized water, wherein the masses of indium nitrate powder and thiourea powder were 0.027 g and 0.01 g, respectively.

[0099] Weigh 0.01 g of indium sulfide nanoparticles and ultrasonically disperse them in 10 mL of ethanol solution. Take 50 μL of indium sulfide ethanol solution and drop it on the TiO2@PDA film on the conductive surface of FTO glass. Dry it at 60°C for 1 h, and repeat this operation 3 times. Finally, put the sample conductive surface upward into a muffle furnace and keep it at 350°C for 30 min.

[0100] The FTO conductive glass is suspended above the mixture of titanium dioxide and dopamine, with an area of ​​10 mm*8 mm reserved on the liquid surface, and the rest of the FTO conductive glass is vertically inserted into the mixture.

[0101] The size of FTO conductive glass is 10 mm*25 mm*2 mm.

[0102] Before use, FTO conductive glass needs to be ultrasonically cleaned with acetone and ethanol for 3 times each. The surface is clean and free of impurities, and then blown dry with nitrogen for later use.

[0103] (3) Implementation of photoelectrochemical cathodic protection technology

[0104] Using sunlight or simulated sunlight to directly irradiate the In2S3 / TiO2@PDA semiconductor photoanode, indium sulfide is prompted to produce photogenerated electrons; copper wires are used to connect the conductive surface of FTO conductive glass and the surface of Q345 carbon steel to establish an electron transmission channel between the semiconductor and carbon steel, thereby realizing the photoelectrochemical cathodic protection of Q345 carbon steel by the indium sulfide semiconductor photoanode.

[0105] The FTO conductive glass and Q345 carbon steel are connected with copper wire and regarded as a conductive whole.

[0106] The copper wire connection method is to use a copper wire with iron alligator clips at both ends, one alligator clip is clamped to the part not covered by the FTO conductive glass, and the other alligator clip is clamped to the part of the Q345 carbon steel not covered by the water-based acrylic resin.

[0107] Comparative Example 1

[0108] Referring to step (2) and step (3) in Example 1, a system for photoelectrochemical cathodic protection of Q235 carbon steel using indium sulfide without a silane coupling agent was constructed.

[0109] (1) Preparation of indium sulfide semiconductor photoanode:

[0110] Indium sulfide semiconductor photoanode was prepared by hydrothermal method.

[0111] The indium sulfide precursor solution and FTO conductive glass were placed in a high-pressure reactor with a capacity of 50 mL of polytetrafluoroethylene substrate, heated at 180°C for 8 h, cooled, and rinsed with deionized water to obtain an indium sulfide semiconductor film on the surface of the FTO conductive glass.

[0112] The indium sulfide precursor solution is prepared by completely dissolving indium nitrate powder and thiourea powder in 25 mL of deionized water, wherein the masses of indium nitrate powder and thiourea powder are 0.045 g and 0.023 g, respectively.

[0113] The size of FTO conductive glass is 10 mm*25 mm*2 mm.

[0114] Before use, FTO conductive glass needs to be ultrasonically cleaned with acetone and ethanol for 3 times each. The surface is clean and free of impurities, and then blown dry with nitrogen for later use.

[0115] Before placing the FTO conductive glass in the reactor lining, the top needs to be wrapped with raw tape; the purpose is to reserve the conductive surface on the top that is not covered by the sample to facilitate the subsequent connection of the copper wire.

[0116] The FTO conductive glass is placed in the reactor lining with the conductive surface facing downward against the inner wall of the reactor and immersed in the mixed precursor solution.

[0117] The indium sulfide semiconductor film was rinsed with deionized water and then dried at 50 °C under vacuum for 6 h.

[0118] (2) Implementation of photoelectrochemical cathodic protection technology

[0119] The indium sulfide semiconductor photoanode is directly irradiated with sunlight or simulated sunlight to induce indium sulfide to generate photogenerated electrons. The conductive surface of FTO conductive glass and the surface of Q235 carbon steel are connected by copper wire to establish an electron transmission channel between the semiconductor and carbon steel, thereby realizing the photoelectrochemical cathodic protection of Q235 carbon steel by the indium sulfide semiconductor photoanode.

[0120] The FTO conductive glass and Q235 carbon steel are connected with copper wire and regarded as a conductive whole.

[0121] The copper wire connection method is to use a copper wire with iron alligator clips at both ends, one alligator clip is clamped to the part of the FTO conductive glass not covered with indium sulfide, and the other alligator clip is clamped to the part of the Q235 carbon steel not covered with the silane coupling agent.

[0122] The size of Q235 carbon steel is 10 mm*25 mm*1.5 mm.

[0123] Q235 carbon steel was mechanically polished and cleaned with organic solvents before use. The metal surface was polished with 200 mesh, 400 mesh, and 800 mesh sandpaper in turn until there were no obvious scratches on the surface; the sample was ultrasonically cleaned with anhydrous ethanol and acetone organic solvents in turn for 15 minutes. After cleaning, the sample surface was blown dry with nitrogen and placed in a vacuum drying oven at 50°C for 6 hours. The purpose is to remove impurities such as dust and oxide film attached to the metal surface.

[0124] Comparative Example 2

[0125] Referring to steps (2) and (3) in Example 2, a system for photoelectrochemical cathodic protection of Q345 carbon steel using indium sulfide without aqueous acrylic resin was constructed.

[0126] (2) Preparation of In2S3 / TiO2@PDA semiconductor photoanode:

[0127] The FTO conductive glass was immersed in a mixture of titanium dioxide and dopamine and heated at 90°C for 3 h, and then placed in a vacuum drying oven at 60°C for 6 h to obtain a TiO2@PDA film on the surface of the FTO conductive glass.

[0128] The titanium dioxide and dopamine mixed solution was prepared by adding 5 mL of deionized water, 0.015 g of dopamine hydrochloride and 0.20 g of titanium dioxide into a 25 mL round-bottom flask, and ultrasonically treating for 30 min. Then, 0.1 g of hexamethylenetetramine powder was added and dissolved in the solution and mixed evenly to obtain a titanium dioxide and dopamine mixed solution.

[0129] The indium sulfide precursor solution was poured into a 50 mL polytetrafluoroethylene-lined autoclave, heated at 150°C for 1 h, cooled, washed with deionized water, and freeze-dried.

[0130] The indium sulfide precursor solution was prepared by completely dissolving indium nitrate and thioacetamide in 25 mL of deionized water, wherein the masses of indium nitrate powder and thiourea powder were 0.027 g and 0.01 g, respectively.

[0131] Weigh 0.01 g of indium sulfide nanoparticles and ultrasonically disperse them in 10 mL of ethanol solution. Take 50 μL of indium sulfide ethanol solution and drop it on the TiO2@PDA film on the conductive surface of FTO glass. Dry it at 60°C for 1 h, and repeat this operation 3 times. Finally, put the sample conductive surface upward into a muffle furnace and keep it at 350°C for 30 min.

[0132] The FTO conductive glass is suspended above the mixture of titanium dioxide and dopamine, with an area of ​​10 mm*8 mm reserved on the liquid surface, and the rest of the FTO conductive glass is vertically inserted into the mixture.

[0133] The size of FTO conductive glass is 10 mm*25 mm*2 mm.

[0134] Before use, FTO conductive glass needs to be ultrasonically cleaned with acetone and ethanol for 3 times each. The surface is clean and free of impurities, and then blown dry with nitrogen for later use.

[0135] (2) Implementation of photoelectrochemical cathodic protection technology

[0136] The indium sulfide semiconductor photoanode is directly irradiated with sunlight or simulated sunlight to induce indium sulfide to generate photogenerated electrons. The conductive surface of FTO conductive glass and the surface of Q345 carbon steel are connected by copper wire to establish an electron transmission channel between the semiconductor and carbon steel, thereby realizing the photoelectrochemical cathodic protection of Q345 carbon steel by the indium sulfide semiconductor photoanode.

[0137] The FTO conductive glass and Q345 carbon steel are connected with copper wire and regarded as a conductive whole.

[0138] The copper wire connection method is to use a copper wire with iron alligator clips at both ends, one alligator clip is clamped to the part of the FTO conductive glass not covered with indium sulfide, and the other alligator clip is clamped to the part of the Q345 carbon steel not covered with water-based acrylic resin.

[0139] The size of Q345 carbon steel is 10 mm*25 mm*1.5 mm.

[0140] Q345 carbon steel was mechanically polished and cleaned with organic solvents before use. The metal surface was polished with 200 mesh, 400 mesh, and 800 mesh sandpaper in turn until there were no obvious scratches on the surface; the sample was ultrasonically cleaned with anhydrous ethanol and acetone organic solvents in turn for 15 minutes. After cleaning, the sample surface was blown dry with nitrogen and placed in a vacuum drying oven at 50°C for 6 hours. The purpose is to remove impurities such as dust and oxide film attached to the metal surface.

[0141] The photoelectrochemical protection systems containing organic coatings prepared in Example 1 and Example 2, and the photoelectrochemical protection systems prepared in Comparative Example 1 and Comparative Example 2 were tested for their photoelectrochemical cathodic protection performance.

[0142] The photoelectrochemical cathodic protection test device contains two electrolytic cells, namely the corrosion cell and the photocell, which are connected by a salt bridge. The carbon steel and photoanode connected by wires are used as working electrodes, silver chloride is used as the reference electrode, and the platinum sheet (area of ​​1cm*1cm) is used as the auxiliary electrode. Carbon steel, silver chloride reference electrode and platinum sheet auxiliary electrode are inserted into the corrosion cell, and the electrolyte is 3.5 wt% NaCl solution. FTO conductive glass is inserted into the photocell, and the electrolyte is a mixed solution of 0.25 mol / L Na2S and 0.35 mol / LNa2SO3. The light source uses a 300 W Xe lamp with an AM1.5 filter. The changes in the photocurrent-time curve and the photovoltage-time curve under illumination are measured by the CHI 660E electrochemical workstation, where on means that the light source is turned on, that is, there is light, and off means that the light source is turned off, that is, there is no light. The performance test results of the photoelectrochemical cathodic protection coating are as follows:

[0143] Figure 1It can be seen that compared with the Q235 carbon steel surface without silane coupling agent (Comparison 1), the potential of the Q235 carbon steel surface coated with silane coupling agent (Example 1) under simulated sunlight irradiation is obviously negatively shifted. At this time, the cathodic protection potential in Example 1 is reduced to about -0.87 V ( Figure 1 a), indicating that under illumination, photogenerated electrons in Example 1 migrate to the surface of carbon steel, playing a photoelectrochemical cathodic protection role for carbon steel. Under simulated sunlight irradiation, the photocurrent density of Example 1 is greater than 0, while the photocurrent density of Comparative Example 1 is substantially less than 0. At the same time, the photocurrent density of Example 1 is significantly higher than that of Comparative Example 1 ( Figure 1 b), indicating that the indium sulfide photoanode in Example 1 can provide cathodic protection current for the carbon steel coated with silane coupling agent, while the photocurrent provided by the indium sulfide photoanode in Comparative Example 1 is not enough to protect the carbon steel. Figure 2 Can get with Figure 1 Similar results indicate that Q345 carbon steel can obtain better indium sulfide / polydopamine / titanium dioxide photoelectrochemical cathodic protection after coating with water-based acrylic resin.

[0144] from Figure 1 and 2 It can be seen that in Examples 1 and 2, silane coupling agent or water-based acrylic resin is applied on the surface of carbon steel, which can regulate the self-corrosion potential of carbon steel and is conducive to the transfer of photogenerated electrons of indium sulfide to carbon steel; in Comparative Examples 1 and 2, silane coupling agent or water-based acrylic resin is not applied on the surface of carbon steel, and the low self-corrosion potential of carbon steel hinders the transfer of photogenerated electrons of indium sulfide to carbon steel, and the photogenerated electrons transferred to the surface of carbon steel are not enough to resist the corrosion of carbon steel. Therefore, the photoanode can provide cathodic protection for carbon steel in Examples 1 and 2, and the cathodic protection potential of Example 1 is within the cathodic protection potential criterion range; but it is difficult to provide cathodic protection for carbon steel in Comparative Examples 1 and 2. This method can significantly improve the photoelectrochemical cathodic protection provided by semiconductor photoanodes to metals with poor corrosion resistance.

Claims

1. A method for improving the corrosion resistance of metals with poor semiconductor photoelectrochemical cathodic protection, characterized in that: The following steps are involved: (1) Preparation of organic resin: An organic coating is prepared on the surface of a metal with poor corrosion resistance and a position not covered by the organic coating is reserved, the organic coating is cured at room temperature, and an organic coating protective film with a physical shielding effect is formed on the surface of the metal with poor corrosion resistance; a position not covered by the organic coating is reserved on the top of the corrosion-resistant metal surface for copper wire connection; (2) Preparation of semiconductor photoanode: Using a conductive material as a substrate, preparing a semiconductor film on the conductive substrate, and reserving a position on the top that is not covered by the semiconductor film; (3) Photoelectrochemical cathodic protection: Copper wires are used to connect the photoanode and the reserved position on the metal with poor corrosion resistance that is not covered with organic coating, so as to establish an electron transmission channel between the semiconductor and the metal with poor corrosion resistance. Sunlight or simulated sunlight is used to directly irradiate the semiconductor photoanode to prompt the semiconductor to produce photogenerated electrons, thereby realizing the photoelectrochemical cathodic protection of the metal with poor corrosion resistance by the semiconductor photoanode.

2. A method for improving the corrosion resistance of metals with poor semiconductor photoelectrochemical cathodic protection according to claim 1, characterized in that: The organic coating includes acrylic resin, epoxy resin and silane coupling agent; the metal with poor corrosion resistance includes iron and its alloy materials.

3. The method for improving the corrosion resistance of metals with poor semiconductor photoelectrochemical cathodic protection according to claim 1, characterized in that: The conductive material includes FTO conductive glass, ITO conductive glass, and titanium plate; the semiconductor photoanode includes single-element semiconductor, oxide semiconductor, sulfide semiconductor, nitride semiconductor, phosphide semiconductor, and a composite thereof.

4. The method for improving the corrosion resistance of metals with poor semiconductor photoelectrochemical cathodic protection according to claim 1, characterized in that: Iron alligator clips are welded at both ends of the copper wire, one alligator clip is clamped to the conductive surface of the substrate not covered by the semiconductor film of the photoanode, and the other alligator clip is clamped to the surface of the metal not covered by the organic coating.

5. The method for improving the corrosion resistance of metals with poor semiconductor photoelectrochemical cathodic protection according to claim 1, characterized in that: The metal with poor corrosion resistance is mechanically polished and cleaned with an organic solvent before use. The metal surface is polished with sandpaper until there are no obvious scratches on the surface. The sample is ultrasonically cleaned with an organic solvent.

6. The method for improving the corrosion resistance of metals with poor semiconductor photoelectrochemical cathodic protection according to claim 1, characterized in that: Organic coatings are prepared on metal surfaces with poor corrosion resistance by brushing, spraying, dipping, electrophoretic coating or electrostatic spraying.

7. The method for improving the corrosion resistance of metals with poor semiconductor photoelectrochemical cathodic protection according to claim 1, characterized in that: A semiconductor film is prepared on a conductive substrate using a hydrothermal method, a solvent thermal method, an oxidation method, a sol-gel method, a chemical vapor deposition method, a physical vapor deposition method or a combination of the above methods.

8. The method for improving the corrosion resistance of metals with poor semiconductor photoelectrochemical cathodic protection according to claim 1, characterized in that: The preparation of the semiconductor photoanode comprises the following steps: 1) The FTO conductive glass is immersed in a mixture containing titanium dioxide and dopamine and heated. After drying, a TiO2@PDA film is obtained on the surface of the FTO conductive glass; The mass ratio of dopamine hydrochloride, titanium dioxide and hexamethylenetetramine in the titanium dioxide and dopamine mixed solution is (0.1-0.2): (2-4): 1; The FTO conductive glass is inserted into the mixture of titanium dioxide and dopamine, and the reserved area on the liquid surface is not inserted into the mixture; 2) pouring the indium sulfide precursor solution into a high-pressure reactor, heating for reaction, cooling, washing with deionized water, and drying to obtain indium sulfide nanoparticles; The indium sulfide precursor solution is an aqueous solution of indium nitrate and thioacetamide, wherein the mass ratio of indium nitrate to thiourea is (2-3):1; 3) Ultrasonically uniformly dispersing indium sulfide nanoparticles in an ethanol solution to obtain an indium sulfide ethanol solution, wherein the concentration of the indium sulfide ethanol solution is (1-2) g / L; drop-coating the indium sulfide ethanol solution on the TiO2@PDA film on the conductive surface of the FTO glass and drying it; then placing the sample with the conductive surface facing upward in a muffle furnace and maintaining it at 300-400°C for 20-40 minutes to obtain an In2S3 / TiO2@PDA semiconductor photoanode.

Citation Information

Patent Citations

  • NH2-MIL-125 / TiO2 composite photo-anode material as well as preparation method and application thereof

    CN111809188A

  • Method for preparing silane conversion film with cathode protection effect on aluminum alloy surface

    CN111893486A

  • Method for enabling photo-generated cathodic protection to be suitable for protection of low-potential metal and alloy thereof

    CN113088976A

  • Photo-anode film for reinforcing steel bar photoelectric cathode protection and preparation method and application thereof

    CN114057408A

  • Energy storage type semiconductor composite photoanode for metal corrosion protection

    CN115433943A